KESULITAN BELAJAR ANAK USIA 5-6 TAHUN DI TK LAB MODEL MUHAMMADIYAH PONTIANAK KOTA - Marwati, Sri; Yuniarni, Desni; Miranda, Dian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractLearning difficulties are a disturbance in one or more of the basic psychological processes that include understanding and use of speech or writing language." In this respect, there is a learning difficulty experienced by kindergarten-age children, which will affect their ability in later classes. This study aims to describe the learning difficulties experienced by children aged 5-6 years in kindergarten Lab. Muhammadiyah Model. Specifically this study describes the difficulty of learning to read children aged 5-6 years, describe the difficulty of learning to write children aged 5-6 years, describe the difficulty of learning to count children aged 5-6 years. The method used is qualitative research method with case study approach. The data source consists of 2 teachers in groups of children aged 5-6 years, 3 parent case subjects, and 3 children who are guilty of learning difficulties which is the subject of the case in this study. After the data is collected, the data is presented for conclusion. Difficulty learning to read on troubled child in 5-6 years age group that is different, class writing process have difficulties, which influence in learning activity class, like inconsistent in the form of letter, when writing have bad writing. The class counting process has difficulties, which affect it in classroom learning activities, such as being able to arrange numbers, and difficulty with almost identical numbers. Based on the results of the study there are several suggestions that can be considered by the parties concerned in an effort to overcome the learning difficulties of children. The suggested suggestions are for teachers to be more familiar with the child's parents, for the kindergarten to be able to carry out joint evaluations on a regular basis, and for parents to be expected to pay attention to the child while at home.Â Kata kunci: kesulitan belajar, kesulitan membaca, kesulitan menulis, kesulitan berhitungÂ